Correction: Viveros-Paredes et al. Neuroprotective Effects of β-Caryophyllene against Dopaminergic Neuron Injury in a Murine Model of Parkinson's Disease Induced by MPTP. Pharmaceuticals 2017, 10, 60 - Juan M. Viveros-Paredes; Rocio E. González-Castañeda; Juerg Gertsch; Veronica Chaparro-Huerta; Rocio I. López-Roa; Eduardo Vázquez-Valls; Carlos Beas-Zarate; Antoni Camins-Espuny; Mario E. Flores-Soto (MDPI AG, 2024)
In the original publication [...]